Second Five Year Plan Progress Report 1959-60 Government of Madhya Pradesh - Planning Commission (Planning Commission, 1959)
The Second Five Year Plan activities received a good momentum with bumper harvest in 1956-57 along with substantial gains in industrial production. Adverse weather conditions and partial failures of rainfall in some parts of the State during 1957-58, however, resulted in substantial contraction in the availability of food-grains during 1958-59. Coinciding with this the decline in the domestic production of manufactures and consumer goods consequent to severe restrictions on import of raw materials and components spurred the prices to new heights with their inevitable projections on the cost of living of the majority of population, cost of production of home-made goods and export trade.
Government of Madhya Pradesh, Directorate of Economics and Statistics